Here comes the fudge - Coco, Nancy (Coco, Nancy. Candy-coated mystery., 2021)
When her best friend's fiancé Shane, a crime scene investigator, is accused of murder, Allie vows to find the truth before the ceremony turns into a jailhouse wedding.